PENEGAKAN KODE ETIK TERHADAP HAKIM YANG MELAKUKAN KOMUNIKASI DENGAN PIHAK YANG BERPERKARA DI LUAR PERSIDANGAN - Tia Ningsih; Puti Priyana (Fakultas Hukum Universitas Islam Syekh Yusuf, 2022)
In carrying out their duties and functions, judges and constitutional judges are required to comply with the Code of Ethics and the Code of Conduct for Judges. However, in reality there are still many judges who violate the code of ethics and the judge's code of conduct. The normative juridical research method is legal research conducted by examining library materials or secondary data in the form of laws and regulations, books, scientific journals, electronic newspapers, legal magazines, the internet, and the Big Indonesian Dictionary. The regulation of the Code of Ethics for Judges in Indonesia is regulated in a Joint Decree of the Chief Justice of the Supreme Court of the Republic of Indonesia and the Chairman of the Judicial Commission of the Republic of Indonesia Number: 047/KMA/SKB/IV/2009 - 02/SKB/P.KY/IV/2009 concerning the Code of Ethics and Code of Conduct Judge. In the event that a judge communicates with the litigating party outside the trial, the settlement is by way of an examination by the Supreme Court and/or the Judicial Commission. Keywords: Code of Professional Ethics, Law, Judge.